SELF-EFFICACY AS A PREDICTOR OF ACADEMIC ACHIEVEMENT IN BASIC SCIENCE AND TECHNOLOGY AMONG STUDENTS IN ANAMBRA STATE (UNIZIK Journal of STM Education, 2025)
The study examined self-efficacy as a predictor of academic achievement in basic science and technology among students in Anambra State. The study was guided by two research questions, and two hypotheses (tested at 0.05 level of significance). The study is a correlational research which adopted a predictive design. The study population comprised of 6250 Upper Basic 8 Students from 20 public schools from 267 schools in the state. Using multistage, purposive sampling technique, proportionate stratified random sampling technique and simple random sampling technique, an education zone and a total sample size of 376 (170 males and 206 females) were drawn from the population. One research instrument, Self Efficacy scale for Basic Science and Technology instrument (SESBST) adapted from Gafoor and Ashraf’s (2006) Self- Efficacy Scale was given out to respondents. Academic achievement was measured using Basic Science and Technology test score of students provided by the teachers. Research instrument was validated by three experts; two from the Department of Science Education and one expert in Measurement and Evaluation unit of the Department of Educational Foundations, all in Nnamdi Azikiwe University Awka, and internal consistency was established using Cronbach’s alpha. The overall reliability coefficient of the instrument was found to be 0.99 for SESBST. Data collected from respondents were analyzed using regression statistical method and Hayes Process. Linear Regression was used to answer the research question one while Hayes Process was used to answer research question two. ANOVA Regression was used to test null hypothesis one at 0.05 level of significance while Hayes process was used to test hypothesis two at 0.05 level of significance. Findings show that self-efficacy significantly predict academic achievement among upper basic 8 Basic Science students in Awka Education Zone. Further analysis revealed that the moderating influence of gender on students’ self-efficacy in predicting their academic achievement in basic science and technology is significant. This implies that teachers should prioritize the development of students’ self efficacy while future researchers could examine whether increasing self-efficacy causes improvements in achievement. Based on research findings, it was recommended that Basic Science and Technology teachers should provide mastery experiences by designing hands-on activities and experiments that students can successfully complete to boost their beliefs in themselves (self-efficacy) and also show students examples of peers and role models successfully engaging in science and technology so as to boost self-efficacy.
Keywords: Self-efficacy, Academic Achievement, Gender, Science and Technology